Relations between perceived problem difficulties and scores in problem solving in mathematics - Sison, Corazon Frial 1952- (1977)
This study was undertaken to determine whether student's perceived problem difficulties are related to their scores in problem solving in mathematics. The study was conducted on four comparable groups of third year high school students of the Colegio de la Purisima Concepcion High School Department, Roxas City in July 1977. Altogether, 172 students and 5 mathematics teachers participated in the study. The research instrument was a 10-item test on solving word problems which was constructed by the researcher. A 7-point scale was used for rating the difficulty of each problem and the certainty rating for each problem. A significant relation between students and teachers' perception of the difficulty of a problem and the number of students who got the problem right in the actual problem solving was found.